Adoption of Mobile Payments in Brazil: Technology Readiness, Trust and Perceived Quality - Tharcisio Alexandrino Caldeira; Jorge Brantes Ferreira; Angilberto Freitas; Roberto Pessoa de Queiroz Falcão (BBR: Brazilian Business Review)
This research investigates the influence of technology readiness on the acceptance of mobile payment services in Brazil, a growing technology within payment methods. The study analyses the relationship between constructs widely used in the literature on technology acceptance - such as perceived usefulness and perceived ease of use - and constructs related to financial services, such as trust and perceived quality. It also evaluates how technology readiness (Parasuraman, 2000) influences these constructs. The authors conducted a survey with 402 participants to test the proposed model, analyzing the data via structural equation modeling (SEM). The results showed that trust, usefulness, and perceived quality of mobile payment services directly influence mobile payment acceptance.